Prospek Peningkatan Kualitas Ruang Perumahan dan Pemukiman yang Berbasis pada Komunitas Studi Kasus: Lingkungan Permukiman Jalan Gagak - Bandung - Suparti Amir Salim; Syahyudesrina Syahyudesrina; Samsirina Samsirina; Fenita Indrasari (ITB Journal Publisher, LPPM ITB, 2008)
This study looks to understand more on the possibility of improving the quality of housing environment based on community initiative that sustain residents' effort to accommodate changes of their surroundings, by observing housing-environment at jalan Gagak